Le port antique de l’agglomération des Mureaux (Yvelines) - Jean-Michel Morin (Gallia)
The origins of the small Gallo-Roman town of Les Mureaux (between 10 and 15 ha) and its port lie in a grouped settlement established during La Tène C1 period on an island of the Seine river. This settlement was located at the crossroads of the route connecting Orléans/Cenabum to Beauvais/Bellovacum and the Seine river, which marked the boundary between the territories of the Carnutes and the Veliocasses. The economic activities and the development of the La Tène period settlement are linked to the river, but the earliest subtle traces indicating the presence of a port are dated to the 1st c. AD. The port was built on a second island, occupying a former residential area, created around the mid-1st c. BC. Around 40-50 AD the port complex was extensively developed using stone masonry. It apparently covered the entire island, i.e. an area encompassing approximately 8,000 m2. Its setting took advantage of an active channel on its right bank and of a dead arm on its left bank. The port was thus located at the transition between terrestrial and waterway lines of communications and also between the core of the Gallo-Roman city positioned on the left bank and the former La Tène insular settlement, which became a craftsman’s quarter, protected against flooding by an artificial terrace of around 5,000 m2. Within this craftsman’s quarter, fishery, butchery, tannery, pottery workshops, glasswork and metallurgy activities are attested. The port is composed of terraces built with caissons maintained by 1 to 2 m wide stone walls. Reinforced on their face with wooden pillars, they form quays on the river front. The northern face is rectilinear and punctuated by at least four quays and terraces and by two basins that open onto the river. The dead arm was transformed into a big basin of shallow water with mooring places. Two parallel streets; one of which is the cardo maximus with its bridge, crossed the port and connected the lower zones of the banks, terraces and the storage areas. Well integrated within the urban fabric and displaying distinct monumentality, this port expresses the ambitions of this small town’s local officials at the boundary of the Civitas Carnutorum, during the 1st c. AD. The port was further developed and extended during the second half of the 1st c. AD and the beginning of the 2nd c. AD. But the complex was gradually abandoned from the end of the 1st c. AD and definitely during the mid-2nd c. AD, at the same time as the dead arm was completely silted up. To date, no other port facilities have been identified for this town. On the contrary, this abandonment, combined with the abandonment of the craftsman’s quarter on the island and several other quarters, seems to indicate a decline, however, at an earlier date than was the case for most of the small cities in Roman Gaul. Nonetheless, the city survived during the Late Roman Imperial period although in a smaller form. During the 4th c. AD the northern bank of the former craftman’s quarter was subject to a small-scale consolidation, whereas significant occupation of the riverbanks resumed in the second half the 5th c. AD with the erection of new buildings at the former port location. During the 9th c. AD a defensive ditch demarcated a portus, several buildings of which were founded on the Roman quays. This port was abandoned at the beginning of the 11th c. AD when the principal core of the settlement moved to the right bank of the river.